2021
DOI: 10.1093/bbb/zbab209
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of indigo-reducing bacteria and analysis of microbiota from indigo fermentation suspensions

Abstract: In natural indigo dyeing, the water-insoluble indigo included in the composted indigo leaves called sukumo is converted to water-soluble leuco-indigo through the reduction activities of microorganisms under alkaline conditions. To understand the relationship between indigo reduction and microorganisms in indigo-fermentation suspensions, we isolated and identified the microorganisms that reduce indigo and analyzed the microbiota in indigo-fermentation suspensions. Indigo-reducing microorganisms, which were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The period from the fermentation preparation to indigo reduction initiation differs depending on the procedure and quality of raw materials. Transitional changes in the redox state of indigo may be related to changes in the microbiota, which is in turn, associated with the indigo reduction initiation, as previously have suggested using clone library analysis (Aino et al, 2010) and nextgeneration sequencing (Tu et al, 2019a(Tu et al, ,b, 2021Lopes et al, 2021Lopes et al, , 2022Nakagawa et al, 2022). On days 0-1, oxygen metabolizable Bacillaceae (e.g., Sutcliffiella cohnii) and Actinobacteria (e.g., Nocardiopsis ganjiahuensis) appear, following which their numbers significantly decrease during days 2-10 as the redox potential (ORP) decreases due to their consumption of oxygen.…”
Section: Introductionmentioning
confidence: 79%
“…The period from the fermentation preparation to indigo reduction initiation differs depending on the procedure and quality of raw materials. Transitional changes in the redox state of indigo may be related to changes in the microbiota, which is in turn, associated with the indigo reduction initiation, as previously have suggested using clone library analysis (Aino et al, 2010) and nextgeneration sequencing (Tu et al, 2019a(Tu et al, ,b, 2021Lopes et al, 2021Lopes et al, , 2022Nakagawa et al, 2022). On days 0-1, oxygen metabolizable Bacillaceae (e.g., Sutcliffiella cohnii) and Actinobacteria (e.g., Nocardiopsis ganjiahuensis) appear, following which their numbers significantly decrease during days 2-10 as the redox potential (ORP) decreases due to their consumption of oxygen.…”
Section: Introductionmentioning
confidence: 79%
“… Enterococcus is chemo-organotrophic facultative anaerobic bacteria that produces lactic acid as the end product ( 34 ). Some Enterococcus species were first found to be provided with indigo-reducing activities ( 35 ). The appearance of the obligate anaerobe Turicibacter ( 36 ) might result from the decrease in the redox potential, but the function of Turicibacter in indigo fermentation remains to be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Transitional changes in microbiota in indigo fermentation employing sukumo have been analyzed using PCR-DGGE and clone libraries analysis [2] and NGS in small-scale fermentation in the laboratory [9][10][11][12][13][14]. In addition to these uncultured procedures, indigo-reducing bacteria have been isolated [1,15]. The reduction in indigo was not always observed in the presence of indigo-reducing species.…”
Section: Introductionmentioning
confidence: 99%
“…However, as NAD(P)H is required for intracellular metabolisms, it is difficult to explain the transfer of intracellular electron donors to extracellular electron accepters via an enzyme accepting electrons from intracellular NAD(P)H. Nicholson and John reported that indigo particle size decreased when the particles were incubated with the culture supernatant from Clostridium isatidis [14]. In addition, Nakagawa et al found that anthraquinone (AQ) is an effective mediator of indigo reduction activity in various indigo-reducing bacterial strains [15]. These results suggested that indigo reduction occurred via an extracellular mediator in the fermentation fluid.…”
Section: Introductionmentioning
confidence: 99%